A Pulsar Vector Observation-Based Link Acquisition Method for X-Ray Communications - Shibin Song; Xiao Lu; Haixia Wang (International Journal of Aerospace Engineering)
X-ray communication (XCOM) is an emerging laser communication technique for deep space applications. Traditional link acquisition of laser communications depends significantly on Earth support and shows little autonomy. For XCOM, a pulsar vector observation-based link acquisition method is proposed, which utilizes noncooperative pulsars in deep space as beacons to acquire absolute attitude information and accomplish link acquisition. Firstly, a pulsar vector observation model was established based on the coordinate definition of the X-ray detector and X-ray collimator model. Secondly, a modified “success-failure” pulsar vector search algorithm with two degrees of freedom was proposed to acquire the pulsar vector. With the pulsar vector and the relative attitude obtained from inertial sensors, the link acquisition pointing vector could be determined. Finally, the performance of the proposed method was evaluated using numerical experiments, and factors that influence the performance are discussed and analyzed.